Didrogesteron use in multiple pregnancy - I O Bushtyreva; N B Kuznetzova; A V Kovaleva; A V Bushtyrev; M P Dmitrieva (IP Berlin A.V., 2015)
Multiple pregnancy is a pregnancy of high risk, as it demands careful observation in highly specialized medical centers (regional perinatal centres), that possess required experience, material and technical potential and human resources.Aim of the study: to evaluate the effectiveness of didrogesteron (Dufaston) use in pregnant women with twins.Materials and methods: we studied 257 pregnant women with twins, that were observed and delivered in perinatal center. 99 pregnant women recived didrogesteron 10 mg twice a day till 20 weeks of pregnancy to provide first wave of tromboplast invasion.Results: administration of didrogesteron to pregnant women with twins decreased the pregnancy of preterm birth. Besides, it became possible to transfer thetime of delivery from early preterm birth (28,0-33,6 weeks) to preterm birth (34,0-36,6 weeks). That is very important for the condition of premature infants.